The Egehøj Cereals: Bread Wheat (Triticum aestivum s. l.) in the Danish Early Bronze Age - Rowley-Conwy, Peter (Journal of Danish Archaeology, 1984)
The Egehøj Cereals - Bread Wheat (Triticum aestivum s. l.) in the Danish Early Bronze Age